Daily variations of temperature, salinity, dissolved oxygen and chlorophyll a, in a hypersaline lagoon of the Gulf of California - JE Valdez-Holguín (Ciencias Marinas, 1994)
Time series of temperature, salinity, dissolved oxygen and chlorophyll a were obtained during one year in La Cruz Lagoon, Sonora (Mexico), in order to know the processes that generate variability in the lagoon. Spectral analysis of these time series showed that the variability was associated to processes with periods of 3 to 15 days. These fortnightly periods are related to spring and neap tide cycles, and the three-day periods are due to wind and/or differences in the sampling hour. The flux index (intertidal volume to total volume ratio) estimated for this lagoon is high, and it can be considered that the circulation and variability of this lagoon are determined by the sequence of the spring and neap tide cycles.